2011
DOI: 10.1111/j.1467-971x.2011.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Asian varieties of English: Attitudes towards pronunciation

Abstract: According to previous studies, Japanese EFL learners who wish to acquire American or British English pronunciation are reluctant to speak their L1-accented English. In view of this tendency, the present study examined the attitudes of Asian learners toward their L1-accented English. University students from Japan, South Korea, and Malaysia evaluated their English pronunciation by responding to a questionnaire. The results of the survey revealed the extent to which their acceptance of their English accents diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 17 publications
3
100
4
1
Order By: Relevance
“…Iimura and Kimizuka (2011) reported in their study of 16 Japanese international students that these participants did not show negative attitudes toward Japanese English. However, the findings from these two studies are at odds with the fındings of previous studies (Fraser, 2006;Matsuda, 2003;Tokumoto & Shibata, 2011) which all suggested that Japanese learners of English view Japanese English negatively as a language variety.…”
Section: Learner Perceptions Of Varieties Of English and Oral Assessmentcontrasting
confidence: 56%
“…Iimura and Kimizuka (2011) reported in their study of 16 Japanese international students that these participants did not show negative attitudes toward Japanese English. However, the findings from these two studies are at odds with the fındings of previous studies (Fraser, 2006;Matsuda, 2003;Tokumoto & Shibata, 2011) which all suggested that Japanese learners of English view Japanese English negatively as a language variety.…”
Section: Learner Perceptions Of Varieties Of English and Oral Assessmentcontrasting
confidence: 56%
“…This finding is perhaps surprising given the results of equivalent studies undertaken in Japan (McKenzie, 2008a(McKenzie, , 2010Tokumoto and Shibata, 2011), China (Xu et al, 2010), South Korea (Yook and Lindemann, 2013) and Oman (Buckingham, 2015) where university students were repeatedly found to rate the status of their own forms of English significantly less positively than L1 English speech, though in some cases again significantly more favourably than Chinese and Indian English (McKenzie and Gilmore, 2015 early view). Table 2, again demonstrated comparatively favourable warmth ratings for the Thai English speaker, and significantly higher than the Indian, Japanese, Mid-West US and Chinese speakers.…”
Section: Speaker Evaluationsmentioning
confidence: 48%
“…Jenkins, 2007;Kachru, 1982;McKenzie, 2008;Tokumoto & Shibata, 2011). Judgments about spoken varieties of English, as Tokumoto and Shibata (2011) explain, are connected to the often made categorization of English users into 'native speakers' (whose accent is described as 'standard) and 'non-native speakers' (considered to speak with a 'non-standard' accent). Notwithstanding the global spread of English and the diversity of its users, 'proper' English is still seen as the prerogative of the UK and US (Jenkins, 2007).…”
Section: Attitudes Towards Spoken Englishmentioning
confidence: 99%
“…In the context of different varieties of English, language attitudes have been studied especially by scholars interested in 'world Englishes' (e.g. Jenkins, 2007;Kachru, 1982;McKenzie, 2008;Tokumoto & Shibata, 2011). Judgments about spoken varieties of English, as Tokumoto and Shibata (2011) explain, are connected to the often made categorization of English users into 'native speakers' (whose accent is described as 'standard) and 'non-native speakers' (considered to speak with a 'non-standard' accent).…”
Section: Attitudes Towards Spoken Englishmentioning
confidence: 99%